Integrasi Fikih dan Kesehatan Masyarakat dalam Perlindungan Kesehatan Ibu dan Anak: Perspektif Maqāṣid al-Syarī‘ah - Rahman R, Abd; Arranury, Zilfadhilah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Maternal and child health is a strategic indicator in public health development because it is directly related to the quality of human resources and generational sustainability. From an Islamic perspective, efforts to maintain maternal and child health are not only of social and medical value, but also represent the implementation of the objectives of Sharia (maqāṣid al-syarī‘ah), particularly the protection of life (ḥifẓ al-nafs), offspring (ḥifẓ al-nasl), and reason (ḥifẓ al-‘aql). This study aims to analyze the role of fiqh in supporting maternal and child health programs through the maqāṣid al-syarī‘ah approach in the context of public health. This study uses a qualitative method with a normative-theological approach, through a review of classical and contemporary fiqh literature and an analysis of public health policies related to maternal and child health. The results of the study show that the principles of maqāṣid al-syarī‘ah are substantively consistent with promotive and preventive strategies in public health, such as pregnancy planning, regular pregnancy check-ups, safe childbirth, and exclusive breastfeeding. In addition, fiqh provides an ethical and normative framework for medical decision-making involving mothers and children, including the use of contraception, cesarean section, and neonatal care. These findings confirm that the integration of maqāṣid al-syarī‘ah into public health policies and practices can strengthen a holistic, equitable approach to health care that is in harmony with spiritual values and universal health principles.